SELECTIVE DYNAMICS RELEASING FRAME KNOW HOW & WHY - Montenegro Joo, Javier (2004)
The Selective Dynamics Releasing Frame (SDRF) algorithm was created sorne time ago by the author ofthis paper to speed-up the computer simulations of stochastic aggrcgation of diffusing particles and to reduce the number of preferred directions of growth anomaly resulting when these símulations are executed with the traditional DLA algorithm. In this papera detailed study ofthe SDRF, carried out to become acquaintcd thoroughly with thc cffects ofits number of arc-segments (frame.s) on the morphology of the resulting aggregates, is reported. The reduction power of the SRDF conceming the number of preferred directions of growth in the rcsulting aggregates is investigated. Simulations of 250 stochastic aggregations of diffusing particles were carried out varying the number of frames in the SDRF. The resulting average fractal dimensions, densitíes and radíí of the aggregates are analysed and reported. Also the observed fluctuations and general evolution of the aggregates is discussed. The use of a Seminal Group of particlcs instead of a single seed is introduced to improve the growth simulations.